Critérios para a amostragem de lianas: Comparação e estimativa da abundância e biomassa de lianas no Cerrado - Carvalho, Paula Guimarães; van Melis, Juliano; Morellato, Leonor Patrícia [UNESP]; Guaratini, Maria Tereza Grombone (FapUNIFESP (SciELO), 2013)
Lianas play a key role in many tropical forests ecosystems, contributing to community abundance, diversity and structure. Techniques to census lianas and estimate biomass have been used mainly in tropical forests. The aim of this study was to verify if different measurement location on the stem and inclusion criteria influence the estimations of liana abundance and biomass in Cerrado. The study was carried out at Itirapina fragment (ca 260 ha) located in São Paulo, Southeast Brazil. We measured all apparent ramets of rooted lianas by using different inclusion criteria: ≥ 0.5 cm in diameter at 30 cm basal area (D_30), and at 130 cm diameter breast height (DBH), in 36 transects (10 × 25 m). We compared the biomass using the allometric equation based on data from tropical florest take at 130 cm (DBH) and other The allometric biomass equation development to estimate the aboveground biomass of live lianas in tropical forests (DAP = 130 cm) was used. We tested the liana biomass, based on measurements taken at (D_30) using two different conversion equations. The results did not show significant differences in liana abundance and above ground biomass estimated applying the different criteria of inclusion However the biomass estimated from data collected at D_30 and converted into DAP showed a tendency to increase in biomass. Our findings suggest that the protocol used to the census of liana and the allometric biomass equation proposed to forests can be applied in the Cerrado.
Criteria for sampling lianas: Comparison and estimation of the liana abundance and biomass in the Cerrado
Keywords: Allometric biomass; Savanna; Vines